Amygdala atrophy affects emotion-related activity in face-responsive regions in frontotemporal degeneration. (September 2016) - De Winter, François-Laurent; Van den Stock, Jan; de Gelder, Beatrice; Peeters, Ronald; Jastorff, Jan; Sunaert, Stefan; Vanduffel, Wim; Vandenberghe, Rik; Vandenbulcke, Mathieu
Abstract: In the healthy brain, modulatory influences from the amygdala commonly explain enhanced activation in face-responsive areas by emotional facial expressions relative to neutral expressions. In the behavioral variant frontotemporal dementia (bvFTD) facial emotion recognition is impaired and has been associated with atrophy of the amygdala. By combining structural and functional MRI in 19 patients with bvFTD and 20 controls we investigated the neural effects of emotion in face-responsive cortex and its relationship with amygdalar gray matter (GM) volume in neurodegeneration. Voxel-based morphometry revealed decreased GM volume in anterior medio-temporal regions including amygdala in patients compared to controls. During fMRI, we presented dynamic facial expressions (fear and chewing) and their spatiotemporally scrambled versions. We found enhanced activation for fearful compared to neutral faces in ventral temporal cortex and superior temporal sulcus in controls, but not in patients. In the bvFTD group left amygdalar GM volume correlated positively with emotion-related activity in left fusiform face area (FFA). This correlation was amygdala-specific and driven by GM in superficial and basolateral (BLA) subnuclei, consistent with reported amygdalar-cortical networks. The data suggests that anterior medio-temporal atrophy in bvFTD affects emotion processing in distant posterior areas.